Edukasi dan Pelatihan Budidaya Padi Metode Salibu di Desa Mekarjaya, Kabupaten Sukabumi - Asep Nurhalim; Resfa Fitri; Salahuddin El Ayyubi; Ahmad Syahirul Alim; Aliyya Xaviera (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Rice related issues in Indonesia are characterized by seasonal shortages and price fluctuations influenced by extreme weather conditions, shrinking agricultural land, distribution constraints, and the ongoing dilemma between import policies and rice self sufficiency, despite the frequent occurrence of national rice stock surpluses. These conditions directly affect farmers’ welfare, consumer affordability, and national food security. Mekarjaya Village, located in Warungkiara District, Sukabumi Regency, is an agrarian area that has experienced a decline in the number of active farmers due to high production costs, limited capital, and low farming profitability. At the same time, local rice production remains insufficient to meet community demand, resulting in continued dependence on rice supplies from outside the village. This community service program aimed to introduce the Salibu rice cultivation method as an alternative farming technology that offers greater production efficiency and the potential to increase land productivity. The program was implemented through several stages, including preparation and coordination, community outreach, participatory training, as well as monitoring and evaluation. Program effectiveness was assessed using pre-test and post-test instruments to measure changes in participant’s knowledge and understanding. The results indicated a significant improvement in farmer’s conceptual and technical understanding of the Salibu cultivation method. However, the level of technology adoption remained low, and the initial field implementation conducted by one farmer encountered difficulties due to improper irrigation management. These findings suggest that successful knowledge transfer alone is insufficient to ensure technology adoption and must be supported by continuous technical assistance during the implementation phase. Therefore, future programs should focus on strengthening field-based mentoring and establishing demonstration plots to promote the sustainable adoption of Salibu technology among farmers.